1996
DOI: 10.1192/bjp.168.4.512
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Environmental Strategies and Psychotropic Medication in the Management of Delirium

Abstract: Simple environmental strategies such as limiting changes in staff, minimising noise levels and involving relatives in re-orientation are frequently overlooked in the management of patients with delirium. Our study suggests that the implementation of environmental strategies occurs primarily in responses to behavioural challenges rather than to limit the core features of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 9 publications
3
50
0
2
Order By: Relevance
“…Other studies have also found mixed subtype as the most common. 23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found mixed subtype as the most common. 23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Для больного должно быть создано адекватное окруже-ние, с минимальным числом смен палаты и место-положения, персонала, низкой освещенностью па-латы по ночам и минимальным уровнем шума. Только в ограниченном числе исследований изучал-ся вопрос об эффективности когнитивных, эмоцио-нальных и средовых вмешательств при лечении де-лирия [55][56][57][58], но такие вмешательства стали стан-дартными рекомендациями, базирующимися на клиническом опыте, здравом смысле и отсутствии побочных эффектов [59].…”
Section: нефармакологические стратегии леченияunclassified
“…66,111 Cognitive impairment in the context of a mild hypoactive subtype of delirium is more likely to be missed. 116 Cognitive screening of cancer patients with a briefly administered instrument such as the Minimental State Examination helps to detect cognitive deficits that otherwise might be missed. 3 This instrument has been widely used, and its psychometric properties are well known.…”
Section: Assessment Of Cognitive Dysfunction In Opioid-treated Patientsmentioning
confidence: 99%
“…• Educate family regarding nature of opioid-related cognitive dysfunction and delirium: psychomotor agitation, perceptual disturbance, delusions, and communication difficulties [107][108][109][110] • Establish goals of care, evaluate pros and cons of intervention in the context of the patient's clinical situation, previously expressed wishes, and family wishes 128 • Monitor delirium severity with an instrument that is either partly 118,119 or wholly observational 42,122,123 • Consider either opioid dose reduction or opioid switch [129][130][131][132][133] • Discontinue or minimize use of all unnecessary medications, especially other psychotropics 4 • Consider all other contributory causes, especially concurrent reversible causes 4 • Assess renal function and adjust dose of opioid or other drugs accordingly [92][93][94][95][96][97] • Assess hydration and supplement with parenteral fluids if necessary 4 • Commence symptomatic treatment of delirium with neuroleptic such as haloperidol 8,150,151 • Environmental manipulation: minimal noise, reorientation, encourage presence of family member 116 • Prevent recurrence: if delirium is reversed, address risk factors for recurrence in future (see Table 6) and emotional lability to be misinterpreted as poor pain control. 108,109 The use of psychostimulants has been advocated in the treatment of opioid-induced sedation, [157][158][159] and cognitive benefit has been demonstrated with neuropsychologic testing in a randomized, doubleblind, placebo-controlled, crossover trial of methylphenidate in patients receiving a continuous infusion of opi...…”
Section: Table 8 Proposed Management Approach To Patients Presenting mentioning
confidence: 99%